(untitled) (Scientific journal of the Fergana State University, 2025)
This article is described the impact of online learning platforms on school students’ education, focusing on student engagement, academic performance, and overall educational outcomes. A survey of 13 participants, including teachers and non-teachers, was conducted to assess perceptions of online learning‘s effectiveness.